Analysis of Carbon Emission Volume, Environmental Performance and Financial Performance of PT Kalbe Farma Tbk - Afriandi Setiawan; , Fanny Ramadhani (Journal of Creative Power and Ambition (JCPA), 2026)
This study aims to analyze the development of carbon emissions, environmental performance, and financial performance of PT Kalbe Farma Tbk during the 2017–2025 period. The research employs a horizontal analysis method with a quantitative descriptive approach. The data used are secondary data obtained from the company’s annual reports, sustainability reports, and the Environmental Performance Rating Program (PROPER) data of PT Kalbe Farma Tbk. The population of this study consists of all financial reports, sustainability reports, and PROPER data of the company, while the sample comprises data from 2017 to 2025. The variables analyzed include carbon emission volume measured by total Scope 1 and Scope 2 emissions, environmental performance measured using PROPER ratings, and financial performance measured by Return on Assets (ROA) and Return on Equity (ROE). The results indicate that PT Kalbe Farma Tbk’s carbon emissions fluctuated throughout the study period, with an overall increasing trend. Environmental performance showed a positive trend, as reflected in the improvement and consistency of the company’s PROPER ratings. Meanwhile, financial performance, represented by ROA and ROE, experienced fluctuations during the observation period. Overall, the findings suggest that PT Kalbe Farma Tbk has demonstrated a commitment to integrating environmental sustainability practices with business operations while maintaining relatively stable financial performance despite various economic and operational challenges.